Damage of Green Synthetic Cement Slurry to Clastic Rock Reservoir - Meng Xu; Xin Tan; Libo Yang; Hanlie Cheng; David Cofell (Journal of Chemistry)
Green synthesis and metal oxide composites have attracted much attention from researchers of industry and academia. As a typical application of green synthesis and metal oxide composites, the protection of oil and gas reservoirs is related to various links such as exploration, drilling, completion, and development. It is a complex and systematic project, which directly affects whether the oil and gas fields can be discovered, evaluated, and efficiently developed in time, and it is also related to the development of oil and gas fields recovery rate. As the most critical part of oil and gas well construction, the cementing process mainly pays attention to the safe pumping of the cement slurry and the long-term effective interlayer isolation capability of the cement sheath. Less attention is paid to the reservoir protection during the cementing process. The high-pressure difference between the annulus and the formation, the high fluid loss, and the high solids content of the cementing slurry during the cementing process have also become major challenges. In order to solve this problem, this study takes a typical clastic rock block in an oilfield in western China as the research object and carries out a geological survey of fracture development, pressure deficit, and cement slurry permeability leakage in the reservoir. The reservoir physical properties, clay mineral characteristics, and formation water quality of rock reservoirs are analyzed. The influence of cement slurry filtrate and solid phase particles on reservoir clay expansion rate and permeability was tested by core porosity and permeability tester. XRD and SEM techniques were used to analyze the damage mechanism of cement slurry filtrate and solid phase particles to the reservoir. The research results show that the average porosity of the clastic rock reservoir in the study area is 15%, the permeability is high, the average pore size of the reservoir is between 37 and 56 μm, the microfractures are developed in the reservoir section, and the porosity and permeability conditions are good; high-valent cations and inorganic ions in the filtrate generate inorganic scales such as CaCO3 and Mg(OH)2 and cross-link with dissolved polymers to form flocculation substances, which cause the filtrate to damage the reservoir, and at the same time, the cement particles in the pore throats in the near wellbore zone are lost along with the leakage. Furthermore, hydration, tightly bonding the inert admixture and the clastic rock formation, forms a tight sealing layer, which reduces the permeability of the reservoir sharply; the expansive clay particles in the reservoir absorb the moisture of the cement slurry filtrate and expand. The volume of the particles increases, and the porous formation containing expansive clay minerals absorbs moisture and causes internal expansion, and the volume expansion rate can reach 9%, which eventually causes the porosity and permeability of the reservoir to decrease, resulting in reservoir damage and solid phase in the cement slurry. The damage of particles to the reservoir is mainly due to the blockage of the reservoir pore throats and the hydration and consolidation of cement particles inside the reservoir caused by the external admixtures in the cement slurry that do not participate in the hydration reaction. The solid phase particles form a filter cake on the surface of the reservoir core and cannot enter the reservoir, but under the condition of porous formation leakage, the solid phase particles with a particle size of 1–10 μm in the cement slurry will directly penetrate into the reservoir rock resulting in shallow plugging in the reservoir near the wellbore. The research results provide theoretical data support for the research on low-damage cementing slurry technology in clastic rock reservoirs. The work provides an important application guidance to green synthesis and metal oxide composites.